Photocytotoxic effect of C₆₀ fullerene against L1210 leukemic cells is accomPanied by enhanced nitric oxide Production and p38 maPk activation - Franskevych, D.V.; Grynyuk, I.I.; Prylutska, S.V.; Pasichnyk, G.V.; Petukhov, D.M.; Drobot, L.B.; Matyshevska, O.P.; Ritter, U. (Experimental Oncology, 2016)
Aim: To estimate the combined action of C₆₀ fullerene and light irradiation on viability of L1210 leukemic cells, nitric oxide (NO) generation, p38 mitogen-activated protein kinase (MAPK) activity and cell cycle distribution. Methods: Cell viability was assessed by MTT test. Light-emitting diode lamp (λ = 410–700 nm, 2.45 J/cm²) was used for C₆₀ fullerene photoexcitation. Nitrite level and NO-synthase activity were measured by Griess reaction and by conversion of L-arginine to L-citrulline, respectively. p38 MAPK activity was assessed by Western blot analysis. Cell cycle distribution was determined by flow cytometry. Results: It was shown that light irradiation of C₆₀ fullerene-treated L1210 cells was accompanied by 55% decrease of their viability at 48 h of culture. Nitrite level measured as an index of reactive NO generation was increased at the early period after C₆₀ fullerene photoexcitation due to activation of both constitutive and inducible NO-synthase isoforms. The simultaneous activation of p38 MAPK was detected. Accumulation of L1210 cells in sub-G₁ phase of cell cycle was observed after C₆₀ fullerene photoexcitation. Conclusion: Photoexcited C₆₀ fullerene exerts cytotoxic effect, at least in part, through triggering production of reactive NO species and activation of p38 kinase apoptotic pathways in L1210 leukemic cells.